EMOTIONAL INTELLIGENCE AND LEADERSHIP STYLE AMONG BULGARIAN FOOTBALL COACHES - Tatiana Iancheva; Gancho Prodanov (Scientific Publishing House. NSA Press, 2019)
Examining the place and influence of emotional intelligence in sports context attracts the attention of a number of researchers. Their surveys are done mostly among athletes and more rarely among coaches. In the last years some researchers have begun to study the relation between emotional intelligence and coaches' leadership style. Authors have found out that emotional intelligence of the coaches was shown to directly predict leadership style and coaching efficacy (Hwang et al., 2013). The aim of the present research is to study the interdependence between Emotional intelligence and Leadership style among Bulgarians football coaches. Methodology: The research was done among 172 football coaches aged between 20 and 56 years, who differ in age, license, age group of their competitors, coaching experience, and sports experience as football players. In order to fulfill the aim of the research we used: 1) Background information, 2) Emotional Intelligence Scale (EIS; Schutte et al., 1998), 3) Revised Leadership Scale for Sport (RLSS; Zhang et. al., 1997). Results: The results reveal that the researched coaches possess the greatest skills in managing their own emotions and the smallest - as regards "Perception of emotions". They most often prefer behavior related to "Training and instruction behavior", choose more seldom Positive feedback behavior, and prefer to take authoritative decisions. We found significant relations between the subscales of Emotional intelligence and Leadership style. Our results did not wholly confirm the results found in literature about the role of Emotional intelligence as a predictor of "Positive feedback behavior" and "Autocratic behavior".